2010
DOI: 10.4049/jimmunol.0903589
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Rejection Triggers the Development of an Aggressive Intragraft Immune Response through Recapitulation of Lymphoid Organogenesis

Abstract: The unwarranted persistence of the immunoinflammatory process turns this critical component of the body’s natural defenses into a destructive mechanism, which is involved in a wide range of diseases, including chronic rejection. Performing a comprehensive analysis of human kidney grafts explanted because of terminal chronic rejection, we observed that the inflammatory infiltrate becomes organized into an ectopic lymphoid tissue, which harbors the maturation of a local humoral immune response. Interestingly, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
129
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(136 citation statements)
references
References 47 publications
7
129
0
Order By: Relevance
“…Ultimately, under a separate set of signals, the plasma cells again migrate from the germinal centers into the medullary region of the spleen and/or leave the spleen and migrate to the bone marrow (46). We envision that, as suggested by others, the cells that compose the lymphoid infiltrates in the kidney produce sufficient signals for self-organization into ectopic lymphoid organs, particularly because there may be sustained antigenic stimulation in transplantation (10). The seeding by these sentinel B cells is followed by largely clonal expansion leading to the formation of nodular clusters that resemble the germinal centers of the spleen.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ultimately, under a separate set of signals, the plasma cells again migrate from the germinal centers into the medullary region of the spleen and/or leave the spleen and migrate to the bone marrow (46). We envision that, as suggested by others, the cells that compose the lymphoid infiltrates in the kidney produce sufficient signals for self-organization into ectopic lymphoid organs, particularly because there may be sustained antigenic stimulation in transplantation (10). The seeding by these sentinel B cells is followed by largely clonal expansion leading to the formation of nodular clusters that resemble the germinal centers of the spleen.…”
Section: Discussionmentioning
confidence: 99%
“…These infiltrates are nodular in appearance and are often referred to as tertiary lymphatic organs, ectopic lymphoid tissue, or lymphoid neogenesis because of their remarkable resemblance to the lymphatic organization seen in the germinal centers of lymph nodes and spleen (8,9). The similarity of these nodules to those in lymphoid organs goes beyond simple morphology in that they include the full spectrum of Tcell, B cell, and dendritic cell components present in the organized nodules of spleen and lymph nodes and have been shown to produce alloantibodies (10,11). Indeed, it has been suggested that the gene expression pattern of the lymphoid infiltrates in rejected kidneys recapitulates the ontogenic program of the embryo during development of the secondary lymphoid organs (10).…”
Section: Transplantation | Combinatorial Antibody Libraries | Next-gementioning
confidence: 99%
See 1 more Smart Citation
“…Tissues derived from kidney transplantation demonstrate that ELFs contribute to germinal centre reactions, local B‐cell maturation and alloimmune responses (anti‐HLA antibody generation). Whereas these observations support a role for ELFs in chronic terminal rejection,120 two studies suggest that ELFs may actual elicit beneficial outcomes 121, 122. These findings in experimental models of kidney and cardiac allografts emphasize that ELF development promotes the recruitment of T cells and B cells displaying inhibitory or regulatory phenotypes 121, 122.…”
Section: Elfs As Perpetuators Of Inflammation‐driven Pathologymentioning
confidence: 94%
“…While the mechanism of chronic kidney rejection is far from certain, recent studies have suggested that a large set of genes that encode proteins of the innate and adaptive immune system are expressed in the host during rejection (2). Another interesting immunological feature of transplanted kidneys is the appearance of highly organized ectopic B-cell clusters in the transplant (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14).…”
mentioning
confidence: 99%